(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper describes the properties of wavelets. The properties and features of conventional wavelets are mentioned. The need of biorthogonal and the concept of biorthogonal wavelets are presented. Though a large number of wavelet functions exist, a specific application may require specialized wavelets in terms of shape, size and smoothness to fulfill the applications’ requirements. In this paper, four new functions were generated and used to represent image data for compression. New conventional biorthogonal wavelets are proposed. The simulation results of the Image compression using new conventional wavelets technique are presented in this paper.